Critical Analysis of Healthcare Accessibility and Addressing Barriers in Urban and Rural Settings - Al Haider, Saleh Hussein Haider; Alshahablah, Ali Nasser Abdullah; Almajeba, Mohammad Hadi Ali; Alyami, Noorah Mohd Hassan; Alshehri, Sarah Ahmad Ali; Al Tarouti, Eman Mohammed; Alramadan, Ameen Ali; Al Bagshi, Baha Ali Hassan; Alnahwi, Ahmed Nasser; Alajmi, Mansoor Mahdi Hadi (Journal of Ecohumanism, 2024)
Accessibility to health care is a fundamental issue on the global agenda due to geographic, economic and systematic differences. Various challenges affect the delivery of Universal health care; these challenges are as follows: The community is a demography whereby urban and rural people have their challenges. FA, despite having a concentration in urban areas, is faced with uniformly high turnout, long duration, and racial bias that is prevalent among Du, Hi, and immigrant people. On the other hand, having a limited number of physicians, weak infrastructure, lack of transport, and insufficient preventive care, rural areas always record a high mortality rate in their communities. This paper analyzes these disparities by comparing and combining quantitative hospital-level healthcare access indicators with qualitative approaches, including patient and provider interviews. A review of the methodological findings presents colossal disparities in infrastructure, human resource distribution, and resource utilization. Accompanying these problems, social factors, such as income, education, and culture, also contribute to people’s health. The solutions include policy interventions in healthcare funding for equal access and developing incentives for human resources in rural areas with telemedicine as a model to overcome the geographical barrier. Haven’t found information on the long-term effects. Yet, it is clear that health education and locally focused approaches are crucial to fixing problems of structural racism. Thus, adopting a contextual and comprehensive approach, this analysis underlines the concerns for developing long-term, effective, and efficient solutions to increase healthcare accessibility for all population groups, irrespective of their locality.